Menghadapi Risiko Pembangunan Bandara Dhoho: Strategi Adaptasi bagi Usaha Mikro, Kecil, dan Menengah di Kediri - Arifiandi, M Arfan (Maliki Interdisciplinary Journal, 2024)
This article analyzes the risks faced by Micro, Small and Medium Enterprises (MSMEs) in Kediri as a result of the construction of Dhoho Kediri Airport. The construction of a new airport can bring significant changes in demand patterns and market preferences, greater competition, changes in infrastructure and logistics, limited resources and capacity, and changes in regulations and policies. MSMEs need to adopt a proactive approach in dealing with this risk by conducting market research, increasing competitiveness, utilizing information technology, preparing business development strategies, monitoring regulatory changes, and collaborating with the government and related institutions. With a better understanding of these risks, it is hoped that MSMEs in Kediri can face change more prepared and take advantage of the opportunities offered by the construction of Dhoho Kediri Airport.